2009
DOI: 10.1016/j.toxicon.2009.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tityus serrulatus scorpion venom on lung mechanics and inflammation in mice

Abstract: The present study evaluated the effects of an intramuscular injection of Tityus serrulatus venom (TsV) (0.67 miocrog/g) on lung mechanics and lung inflammation at 15, 30, 60 and 180 min after inoculation. TsV inoculation resulted in increased lung elastance when compared with the control group (p < 0.001); these values were significantly higher at 60 min than at 15 and 180 min (p < 0.05). Resistive pressure (DeltaP1) values decreased significantly at 30, 60 and 180 min after TsV injection (p < 0.001). TsV inoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In a subsequent step, effective lung resistance (R L ) and elastance (E L ) were computed by linear regression fitting of the recorded signals P tr , V′, and V to the conventional respiratory mechanics model P tr = P o + E L × V + R L × V′, where P o is a parameter to account for the external positive end-expiratory pressure applied by the ventilator. For each animal, R L and E L were computed from data obtained during 5 breathing cycles [21, 22]. …”
Section: Methodsmentioning
confidence: 99%
“…In a subsequent step, effective lung resistance (R L ) and elastance (E L ) were computed by linear regression fitting of the recorded signals P tr , V′, and V to the conventional respiratory mechanics model P tr = P o + E L × V + R L × V′, where P o is a parameter to account for the external positive end-expiratory pressure applied by the ventilator. For each animal, R L and E L were computed from data obtained during 5 breathing cycles [21, 22]. …”
Section: Methodsmentioning
confidence: 99%
“…Paneque Peres et al 2009 [135] shown that the Brazilian scorpion T. serrulatus resulted in increased lung, kidney, liver, and heart inflammation, characterized by an increased density of mononuclear cells after injection in rats. These authors concluded that this venom leads to acute lung injury, characterized by altered lung mechanisms and increased pulmonary inflammation.…”
Section: Organ Dysfunction and The Inflammatory Responsementioning
confidence: 99%
“…Transcriptome analysis showed that sodium channel toxins represent 16% of the transcripts in Ts venom [17]. These neurotoxins disrupt the neuromuscular, cardiovascular, and respiratory systems and elicit a complex pattern of clinical signs and symptoms that can lead to death [9], [24][27]. Other important neurotoxins, which represent 22% of Ts venom transcripts [17], act on potassium channels [28][30].…”
Section: Introductionmentioning
confidence: 99%